Analisis Promosi Terhadap Minat Beli Konsumen Pada Kafe Kulumanu Kopi Kota Tangerang - Genta Ramadhandi; Fadillah Fadillah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to find out about promotions that can increase consumer buying interest at the Kulumanu Kopi Cafe, Tangerang City. The results of observations made by researchers show that consumer buying interest is fluctuating, if seen from good quality products at affordable prices and very strategic locations in the city center close to the Tangerang City square. Promotion is carried out only using word of mouth and Instagram social media. The research method used is descriptive qualitative. This research emphasizes quality, not quantity. Data collection techniques include observation, direct interviews with key informants, focus group discussions (FGD) and documentation. Data analysis techniques use SWOT (Strength, Weakness, Opportunity, Threat) analysis with the IFAS (Internal Factory Analysis Summary) and EFAS (Environmental Factor Analysis Summary) Matrix approaches. The results of the Strength Analysis Research are; Strategic location in the city center, Has AC and Non-AC rooms with attractive interior design, Builds relationships between internal and external cafe employees, Management of activities that always innovate, Has photo box facilities. Weaknesses, namely; Requires large initial capital, Dependence on weather, Lack of menu variety, Limited space. Opportunities in the future are; Cooperating or collaborating with Coffee Shop Brands that are well known in Indonesia and even internationally, Providing a coffee menu with the characteristics of Kulumanu Coffee in various cities in Indonesia and even abroad, opening branches in big cities in Indonesia. Threats from outside that must be anticipated are; There are more and more competitors in the coffee cafe business. Many mobile coffee shops have innovated by selling cafe class coffee at lower prices. Many cafes collaborate with musicians so that every day there is live music in the cafe. Therefore there must always be new innovations. Even though the promotional method used is in accordance with the marketing concept of Kulumanu Kopi Cafe, it must add promotional methods using other social media such as Tiktok, Youtube, Facebook, also using advertisement media and endorsement media by celebgrams, artists/famous figures to introduce Kulumanu Kopi Cafe. in order to increase consumer buying interest).